Ressentiment as Tragic Transformation of the Personal Existence. Phenomenological Interpretation with Scheler and Améry - Velázquez González, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Ressentiment is a complex emotional phenomenon that affects the existential structure of the person who suffers from it: in the way of perceiving, relating with others and finding oneself in a shared world. It is taken in Psychopathology as a maladaptive feature of certain personality disorders, and in Moral Theory it is a negative reaction to positive and vital values—following the partial point of view of Nietzsche, who underestimates the experiences of damage and pain that are in the origin of the experience of resentment. A phenomenological approach to resentful emotional life—in the company of Max Scheler’s Phenomenology and first person account made by Jean Améry—discloses Ressentiment as a metamorphosis of the personal existence, which may also imply a tragical sense. This interpretation of the phenomenon is additionally linked to a breach of the essence of sympathy, as the basic way of the interpersonal relationship, and to its reconstruction, as a basic sense of justice.
Keywords: ressentiment; phenomenology; Scheler; Améry